PSXVI-20 Comparison of zinc finger sequences of PR domain-containing protein 9 between Jianchang horse and Anning pony. (7th December 2018) - Yang, L; Jin, S; Huang, L; Zheng, Y
Abstract: PR domain-containing protein 9 (PRDM9) is encoded by Prdm9 gene, which is the only known speciation gene in mammals, and its terminal zinc finger (ZnF) domain is highly variable and rapidly evolving in mammals. Both Jianchang horse (with average height of 115 cm in adult stallions) and Anning pony are distributed in the same region of Southwest Sichuan Province of China; however, their genetic relationship is unclear. This research characterized the zinc finger domains of Prdm9 gene of Jianchang horse and Anning pony, in order to provide data for their evolutionary study and breeding practice. Genome DNA was isolated from the blood samples of Jianchang horses (n=16) and Anning ponies (n=4). PCR amplification of Prdm9 zinc finger domain demonstrated that most individuals were homozygous consisting of consecutive array of 9 tandemly repeated C2H2 zinc fingers; heterozygous zinc finger domains consisting of both 9 and 11 zinc finger tandem repeats were detected only in two Jianchang horses. This research revealed a total of 14 zinc fingers and the resulting 8 zinc finger domains of PRDM9. Comparison of homozygous PRDM9 showed identical zinc finger domain in nine Jianchang horses and two Anning ponies; however, significant amino acid differences in ZF8 existed between five Jianchang horses and two Anning ponies. In conclusion, the present study found that most horses assayed contained 9 zinc fingers in PRDM9, and sequence alignments of zinc fingers suggested that some Jianchang horses and Anning ponies were highly related and some might have different genetic origins.